Capturing local structure modulations of photoexcited BiVO4 by ultrafast transient XAFS. Issue 53 (8th May 2017) - Uemura, Yohei; Kido, Daiki; Koide, Akihiro; Wakisaka, Yuki; Niwa, Yasuhiro; Nozawa, Shunsuke; Ichiyanagi, Kohei; Fukaya, Ryo; Adachi, Shin-ichi; Katayama, Tetsuo; Togashi, Tadashi; Owada, Shigeki; et al.
Abstract : Femto- and picosecond transient XAFS revealed the photoexcitation dynamics of BiVO4 . Abstract : Ultrafast excitation of photocatalytically active BiVO4 was characterized by femto- and picosecond transient X-ray absorption fine structure spectroscopy. An initial photoexcited state (≪500 fs) changed to a metastable state accompanied by a structural change with a time constant of ∼14 ps. The structural change might stabilize holes on oxygen atoms since the interaction between Bi and O increases.